2016
DOI: 10.1215/9780822375005
|View full text |Cite
|
Sign up to set email alerts
|

Every Last Tie

Abstract: The Feminist Bookstore Movement Lesbian Antiracism and Feminist Accountability kristen hogan From the 1970s through the 1990s more than 100 feminist bookstores built a transnational network that helped shape some of feminism's most complex conversations. Kristen Hogan traces the feminist bookstore movement's rise and eventual fall, restoring its radical work to public feminist memory. The bookwomen at the heart of this storymostly lesbians and including women of color-measured their success not by profit, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This ideologically framed motive was actually a projection of his personal grievances: when his parents separated, the guardianship of Breivik was given to his mother who, according to him, had feminized him. Kaczynski suffered from the fact he left his home and family to join a scientific program at university, and he then developed an ideology of his own, denouncing scientific progress and "technological slavery" (Kaczynski, 2016). Merah, who had not been accepted into the French army, decided to kill soldiers (Merah & Sifaoui, 2012).…”
Section: Narcissistic Rage: From Personal Grievance To Moral Outragementioning
confidence: 99%
“…This ideologically framed motive was actually a projection of his personal grievances: when his parents separated, the guardianship of Breivik was given to his mother who, according to him, had feminized him. Kaczynski suffered from the fact he left his home and family to join a scientific program at university, and he then developed an ideology of his own, denouncing scientific progress and "technological slavery" (Kaczynski, 2016). Merah, who had not been accepted into the French army, decided to kill soldiers (Merah & Sifaoui, 2012).…”
Section: Narcissistic Rage: From Personal Grievance To Moral Outragementioning
confidence: 99%
“…A vast number of studies have been conducted to analyze inherent properties and behaviors found in cities. For instance, multiple metrics have been adopted to explain their structural conditions [3], their intense traffic of vehicles [4], and the emergence of collective behavior [5]. In other studies, the authors centered on the geometrical perspective of the network [6], and on the elements positioning [7,8].…”
Section: Introduction and Related Workmentioning
confidence: 99%